2020
DOI: 10.1002/eap.2099
|View full text |Cite
|
Sign up to set email alerts
|

Disentangling direct and indirect effects of habitat fragmentation on wild plants' pollinator visits and seed production

Abstract: Habitat fragmentation threatens plant and pollinator communities, as well as their interactions. However, the effects of landscape fragmentation on the pollination of wild plant species are not well understood yet, partly because there are many correlated features in fragmented landscapes (e.g., decreased patch size, increased isolation, and patch complexity) whose influences are difficult to disentangle. Using a structural equation modeling approach, we assessed the direct and indirect effects of landscape fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(23 citation statements)
references
References 85 publications
3
20
0
Order By: Relevance
“…Consistent with previous studies in Scandinavia 42 , the relationship of bumblebee abundance and richness with flower density varied along the flowering season, probably because bumblebee populations are much larger in the middle of the season 41,57 and then the resources become more limiting 42 . It is also in concordance with the positive relationship between bumblebee visitation and blooming density found in other studies 15,58,59 , and with a previous study carried out in our study system that showed a strong influence of the flowering resources on the whole pollinator community 5 . It is not surprising that, in systems as the Scandinavian temperate forests, which are generally poor in flowers 60 , flower availability plays such an important role in bumblebee distribution.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Consistent with previous studies in Scandinavia 42 , the relationship of bumblebee abundance and richness with flower density varied along the flowering season, probably because bumblebee populations are much larger in the middle of the season 41,57 and then the resources become more limiting 42 . It is also in concordance with the positive relationship between bumblebee visitation and blooming density found in other studies 15,58,59 , and with a previous study carried out in our study system that showed a strong influence of the flowering resources on the whole pollinator community 5 . It is not surprising that, in systems as the Scandinavian temperate forests, which are generally poor in flowers 60 , flower availability plays such an important role in bumblebee distribution.…”
Section: Discussionsupporting
confidence: 94%
“…However, these important pollinators are suffering worldwide declines 1,2 , which have been mainly attributed to the loss and fragmentation of natural and semi-natural areas due to landuse changes 1,3 . Such negative effects of habitat fragmentation are related to the reduction in the extent of natural habitats 1 , to changes in the quantity and quality of flowering resources 4,5 and nesting sites 6 and their spatial configuration 7 , as well as to changes in habitat edge/area relationships that could affect habitat suitability 8 (see Fig. 1 for a conceptual diagram).…”
mentioning
confidence: 99%
“…For any given area, an increase in the number of different cover types leads to a decrease in the amount of each (Duelli 1997), which might not allow a large growth of populations of species that are benefitted from certain habitats. Finally, as was true for wild bee richness, we also found that flower abundance tended to be positively related to wild bee abundance, supporting the idea that a larger number of flowers in a community attract a larger number of pollinators (Hegland and Boeke 2006, Lázaro et al 2020).…”
Section: Discussionsupporting
confidence: 84%
“…Habitat shape can also have implications as edge length increases as habitats become more complex in shape [25,26]. High edge to area ratios can increase exposure of pollinator populations to pesticides [27] and negative relationships between habitat patch complexity and pollinator visitation have been reported [28]. Conversely, edges themselves can be important pollinator habitats [29].…”
Section: Introductionmentioning
confidence: 99%